Financial Dependence, Formal Credit and Informal Jobs - New Evidence from Brazilian Household Data - Luis Catao; Carmen Pages; Maria Fernanda Rosales (Inter-American Development Bank (IDB), 2009)
This paper examines a much overlooked link between credit markets and formalization: since access to bank credit typically requires compliance with tax and employment legislation, firms are more likely to incur such formalization costs once bank credit is more widely available at lower cost. The relevance of this credit channel is gauged using the Rajan-Zingales measure of financial dependence and a difference-in-differences approach applied to household survey data from Brazil. It is found that formalization rates increase with financial deepening, especially in sectors where firms are typically more dependent on external finance. Also found is that, decomposing shifts in formalization rates into those within each firm size category and those between firm sizes, financial deepening significantly explains the former but not so much the latter. Some key policy implications are derived.
Keywords: E26; G21; O4; O16; 330; Credit Markets; Financial Dependence; Informality; Brazil